Analisis Kinerja Pendampingan Pada Program Pembangunan Dan Pemberdayaan Masyarakat Desa Di Kabupaten Lebong - Zulhakim, Abdul Aziz; Susanti, Is (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Village development based on community empowerment is the desired objective of the P3MD programme, in which the state participates by providing human resources for assistance, known as Technical Assistance Personnel (TPP). TPP, as a transformation of village facilitation, carry out community empowerment activities by assisting, organising, guiding and facilitating villages to develop community self-reliance and welfare by improving knowledge, attitudes and skills. This study aims to describe the performance of local village facilitators in achieving the objectives of the P3MD programme in Lebong Regency. This research is descriptive, combining quantitative and qualitative methods of data collection. The data analysis method used involves organising and sorting the collected data by dividing the research variables into several frequencies and percentages, then analysing and interpreting the obtained data by explaining it in easily understandable sentences. The results show that the majority of local village facilitators have performed their duties well, actively participating in various stages of village development and successfully mobilising community participation. However, some local village facilitators still face challenges such as the lack of clear work plans and inconsistencies in the execution of tasks. It was found that most local village facilitators have a high frequency of visits according to their work plans, but there are still some who are not yet providing optimal support.